(untitled) (Pedagogy of Higher and Secondary Education, 2000)
The outstanding teacher’s contribution into the decision on the problem of attentive pupils’ upbringing is considered in this article. It is the organization of psychologic - pedagogical conditions of preventive measures of using narcotics, asocial actions and pupils’ behavior, and the ways of realization of examination and control as well.